Police recording of custodial interrogations: A state-by-state legal inquiry - Bang, Brandon L. (International journal of police science & management, 2018)
The Supreme Court of the United States recognized in its seminal case Miranda v Arizona, 384 US 436 (1966) that police used overly coercive techniques during custodial interrogations to obtain confessions. Yet, post Miranda, police officers still utilize legal coercive and deceptive techniques during custodial interrogations. Unfortunately, some of these techniques have proven to be so coercive that they lead to false confessions and innocent people being convicted for crimes they did not commit. Some states have taken measures to protect the accused during custodial interrogations and require the police to record custodial interrogations under certain conditions. The policies and procedures that mandate interrogation recording vary in scope and by state. This article sheds light on the different statutes and policies implemented at the state level that regulate custodial interrogation recording.